Transformasi Sistem Penilaian Kinerja Guru melalui Prinsip-Prinsip Manajemen Islami - Dwi Suryani Alfa, Dwi Suryani Alfa; Halida; Jamilus (Indo-MathEdu Intellectuals Journal, 2025)
Teacher performance assessment is important in educational human resource management. However, the implementation of performance assessment in Islamic educational institutions is still administrative and not integrated with Islamic spiritual values and work morality. The purpose of this article is to analyze the transformation of the teacher performance assessment system based on Islamic management principles, such as amanah, justice, ihsan, and accountability. This study uses a qualitative approach based on literature studies. The data sources used are primary data, namely books on performance management theory and articles related to Islamic educational management and teacher performance assessment. Secondary data are in the form of articles on Islamic ethics. The results of the analysis show that the Islamic performance assessment system applies a balance between worldly and hereafter aspects with indicators that include the dimensions of intention, process, and work results. The transformation of the performance assessment system needs to be integrated with the values of tauhid, amanah, and maslahah in the assessment instruments or procedures. Thus, teacher performance assessment is not just an administrative evaluation tool, but also a way of moral development, increasing professionalism, and strengthening spirituality in Islamic educational management.